C / N ratio, stable isotope (δ 13 C, δ 15 N), and n-alkane patterns of brown mosses along hydrological gradients of low-centred polygons of the Siberian Arctic - Zibulski, Romy (Dr.); Wesener, Felix; Wilkes, Heinz; Plessen, Birgit; Pestryakova, Luidmila A. (Prof. Dr.); Herzschuh, Ulrike (Prof. Dr.) (2019)
Mosses are a major component of the arctic vegetation, particularly in wetlands. We present C / N atomic ratio, delta C-13 and delta N-15 data of 400 brown-moss samples belonging to 10 species that were collected along hydrological gradients within polygonal mires located on the southern Taymyr Peninsula and the Lena River delta in northern Siberia. Additionally, n-alkane patterns of six of these species (16 samples) were investigated. The aim of the study is to see whether the inter-and intraspecific differences in C / N, isotopic compositions and n-alkanes are indicative of habitat, particularly with respect to water level. Overall, we find high variability in all investigated parameters for two different moisture-related groups of moss species. The C / N ratios range between 11 and 53 (median: 32) and show large variations at the intraspecific level. However, species preferring a dry habitat (xero-mesophilic mosses) show higher C / N ratios than those preferring a wet habitat (meso-hygrophilic mosses). The delta C-13 values range between 37.0 and 22.5% (median D 27.8 %). The delta N-15 values range between 6.6 and C 1.7%(median D 2.2 %). We find differences in delta C-13 and delta N-15 compositions between both habitat types. For some species of the meso-hygrophilic group, we suggest that a relationship between the individ-ual habitat water level and isotopic composition can be inferred as a function of microbial symbiosis. The n-alkane distribution also shows differences primarily between xeromesophilic and meso-hygrophilic mosses, i. e. having a dominance of n-alkanes with long (n-C29, n-C31 /and intermediate (n-C25 /chain lengths, respectively. Overall, our results reveal that C / N ratios, isotopic signals and n-alkanes of studied brown-moss taxa from polygonal wetlands are characteristic of their habitat.